The half of the story we did not know about prism adaptation. (October 2019) - Facchin, Alessio; Folegatti, Alessia; Rossetti, Yves; Farnè, Alessandro
Abstract: Since 1910 (Helmholtz, treatise on physiological optics), it is known that pointing under deviating prisms induces an initial error in the direction of the deviation, immediately followed by a gradual correction of the error, and an after effect (AE) in the opposite direction after prisms removal, the hallmark of prisms adaptation (PA). Several sensorimotor effects are also produced by PA on proprioceptive, visual and visuo-proprioceptive frames of reference, the latter being called total aftereffect shift (TS) of prism adaptation. Yet, after more than one century, we face a puzzling result: while pointing under prisms exposure, people rapidly achieve an optimal performance and reduce their error by 100%. Invariably, though, when AE is measured (TS) people only show at best 50% of the induced optical deviation, as if the other half was lost somewhere. Here we show that the other half of prism adaptation AE is not lost, and actually emerges clearly and consistently across several experiments when assessing for a so far largely neglected component: the shift induced at the level of the adapted hand. Here we report that this effect is robust and highly specific and we suggest calling it hand-centred aftereffect. These findings reveal that, in PA processes, beside visual and proprioceptive frame of reference, also hand centred ones are involved. Consistently with this view, taking into account the hand aftereffect, the total amount of the aftereffect reaches 76-to-94%, depending on the measure and experiment, thus explaining the largest part of optical shift, previously unnoticed. We suggest this novel aspect of PA would be considered in future clinical studies in relation with responder/non-responder patients' profile to inform integrated models of PA that might allow for optimising patient-tailored PA procedures.